Tradisi Pembakaran Mayat atau Ngaben (Studi Fenomenologi Anggota Keluarga Etnik Bali) - Purnami, Made Dewi; Aryanti, Nina Yudha; Kartika, Tina; Zainal, Anna Gustina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The aim of this research is to find out and analyze the experiences of family members who are prevented from carrying out the Ngaben tradition of their family members in Mataram Udik Village through motifs. This research uses a type of qualitative research using the phenomenological method. Data collection techniques were carried out by means of field observation, interviews with informants and documentation of research results. This research aims to find out more in-depth awareness and analyze the experience of one family member who is hampered by carrying out the Ngaben tradition of his family members. The research results showed that the Balinese ethnic experience regarding the Ngaben tradition in Mataram Udik Village resulted in positive perceptions, because informants were able to carry out mass Ngaben processions after being hampered by economic factors. Informants who were hampered from carrying out the Ngaben carried out the Mekingsan Ring Geni procession, which is a form of cremation ceremony where the spirits are entrusted temporarily to the God of Brahma or the God of Fire before undergoing the next ceremony, namely the Mass Ngaben, so that they can unite with Ida Sang Hyang Widi Wasa/God Almighty. In conclusion, the meaning obtained by the Balinese ethnic group is that the material body or body is nothing but a combination of 5 material elements or Panca Mahabhuta (earth, water, fire, air and ether). Fire has a special status among the Panca Mahabhuta as the purest among the pure, so Fire is used to free the mortal body back to its origin to become the Panca Mahabhuta. Keywords: Balinese Ethnicity, Phenomenology, Ngaben, Experience